2015
DOI: 10.1007/s00414-015-1239-6
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged parietal foramina: a rare forensic autopsy finding

Abstract: Enlarged parietal foramina (EPF) are a quite rare developmental defect of the parietal bone which has to be distinguished from the normal small parietal foramina. We report a forensic case of an individual found in an advanced state of putrefaction in his own house with an undetermined cause of death. No evidence of trauma was observed, and the toxicological exam was negative. The victim was a 40-yearold man with a history of epilepsy. The large biparietal foramina, a rare anatomical variation and unusual auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…16 Because it is autosomal dominant, it can help forensic identification once the relatives of the victims are aware of its existence. 20 On the second cranium, CAV90, the EPFs were not translucent and had different sizes. The average length was 5.0 cm, and the average width was 3.4 cm.…”
Section: Discussionmentioning
confidence: 99%
“…16 Because it is autosomal dominant, it can help forensic identification once the relatives of the victims are aware of its existence. 20 On the second cranium, CAV90, the EPFs were not translucent and had different sizes. The average length was 5.0 cm, and the average width was 3.4 cm.…”
Section: Discussionmentioning
confidence: 99%
“…The EPF is now thought to result from mutations in the homeobox genes ALX4 (located on chromosome 11) and MSX2 (located on chromosome 5) [27][28][29]. Therefore, Durão C et al proposed that decreased identity information could be clarified by forensic identification based on rare anatomical variations of the PF [30]. In addition, studies have found that pathological processes of some diseases may change the diameter and shape of the skull foramina, which may be associated with cranial malformation, cleft lip and palate, craniofacial dysplasia, broad thumb syndrome, hypoplasia of the skull and clavicle, and syndrome consisting of the hypoplastic syndrome [31,32], ocular inflammation, hyperglycaemia, obesity, mental retardation and epilepsy [26].…”
Section: Discussionmentioning
confidence: 99%
“…The posterior interparietal region of the skull has been thought to predispose to a variety of bony variants and congenital anomalies involving the scalp, skull, meninges, and adjacent cerebral cortices. 4,[6][7][8][9][10][11][12][13] In this study, 4% of the identified PF presented an obstruction around the outer opening, which may make it difficult to identify on dry skulls, cadaver specimens, and intraoperative observation. This means that the frequency of the PF may be underestimated for a superficially hidden outer opening.…”
Section: Discussionmentioning
confidence: 99%
“…The region has been known to predispose to a variety of bony variants and congenital anomalies involving the scalp, skull, meninges, and adjacent cerebral cortices. 4,[6][7][8][9][10][11][12][13] Consequently, extensive studies have been conducted on the PFs, cranial sutures associated with the posterior interparietal region, and patterns of developmental ossifications in the region. 12,[14][15][16][17] However, to the best of our knowledge, no study has explored the bony canals of the posterior interparietal region in detail.…”
mentioning
confidence: 99%